Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2009
DOI: 10.1111/j.1365-294x.2009.04355.x
|View full text |Cite
|
Sign up to set email alerts
|

Female philopatry in coastal basins and male dispersion across the North Atlantic in a highly mobile marine species, the sperm whale (Physeter macrocephalus)

Abstract: The mechanisms that determine population structure in highly mobile marine species are poorly understood, but useful towards understanding the evolution of diversity, and essential for effective conservation and management. In this study, we compare putative sperm whale populations located in the Gulf of Mexico, western North Atlantic, Mediterranean Sea and North Sea using mtDNA control region sequence data and 16 polymorphic microsatellite loci. The Gulf of Mexico, western North Atlantic and North Sea populat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

15
137
1

Year Published

2011
2011
2020
2020

Publication Types

Select...
8
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 116 publications
(160 citation statements)
references
References 79 publications
15
137
1
Order By: Relevance
“…Sex-bias in favour of male dispersal has been noted among walruses in Foxe Basin Stewart 1999, Stewart et al 2003). Male-biased dispersal has also been reported from other marine mammals such as Steller sea lions (Eumetopias jubatus; Trujillo et al 2004), southern elephant seal (Mirounga leonina; Fabiani et al 2006), harbour seals (Phoca vitulina; Herreman et al 2009), bottlenose dolphins (Tursiops aduncus; Möller and Beheregaray 2004) and sperm whales (Physeter macrocephalus; Engelhaupt et al 2009). However, suggestions of male-biased dispersal were never reflected by all three different tests used to explore this issue in the present study.…”
Section: Sex-biased Dispersalmentioning
confidence: 65%
“…Sex-bias in favour of male dispersal has been noted among walruses in Foxe Basin Stewart 1999, Stewart et al 2003). Male-biased dispersal has also been reported from other marine mammals such as Steller sea lions (Eumetopias jubatus; Trujillo et al 2004), southern elephant seal (Mirounga leonina; Fabiani et al 2006), harbour seals (Phoca vitulina; Herreman et al 2009), bottlenose dolphins (Tursiops aduncus; Möller and Beheregaray 2004) and sperm whales (Physeter macrocephalus; Engelhaupt et al 2009). However, suggestions of male-biased dispersal were never reflected by all three different tests used to explore this issue in the present study.…”
Section: Sex-biased Dispersalmentioning
confidence: 65%
“…New individuals from the Atlantic Ocean will occasionally enter the Gulf in the winter and join the resident population for a time at their feeding aggregation sites in the De Soto Canyon area in the northern Gulf as well as travel to other areas in the southern Gulf portion. One study that analyzed biparentally inherited nuclear DNA found no significant difference between whales in the North Atlantic and the Gulf of Mexico, suggesting possible migratory exchange of male Gulf sperm whales (Engelhaupt et al 2009). Another study that compared photo-identified sperm whales in the eastern Caribbean with those in the Sargasso Sea and the Gulf of Mexico found no matches, suggesting low to no dispersal (Gero et al 2007).…”
Section: Speciesmentioning
confidence: 99%
“…Since the latter are only available on research or on military vessels, it would be expected that an opportunistic sighting record would underestimate sperm whale preponderance. The Mediterranean population is genetically differentiated from the Atlantic populations and, based on a sample that did not contain LB representatives, has zero mitochondrial DNA diversity [70]. Aharoni [63] documented the only record of sperm whale in the LB prior to the period covered here.…”
Section: Sperm Whalementioning
confidence: 99%